Hepatoprotective effect of Saccharomyces Cervisciae Cell Wall Extract against thioacetamide-induced liver fibrosis in rats. Issue 6 (June 2021) - El-Gendy, Zeinab A.; El-Marasy, Salma A.; Ahmed, Rania F.; El-Batran, Seham A.; Abd El-Rahman, Sahar S.; Ramadan, A.; Youssef, S.A.H.
Abstract: Fibrosis represents a common outcome of almost all chronic liver diseases and leads to an impairment of liver function that requires medical intervention. The current study aimed to evaluate the potential anti-fibrotic effect of Saccharomyces cervisciae cell wall extract (SCCWE) against thioacetamide (TAA)-induced liver fibrosis in rats (200mg/kg b.w. i.p. twice weekly for 6 weeks) using Ursodeoxycholic acid (UDCA) as a reference anti-fibrotic product. SCCWE at two doses (50 and 100 mg/kg) significantly ameliorated the rise in serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma glutamide transferase (GGT) activities, total bilirubin and direct bilirubin, increased total protein and albumin. SCCWE significantly reduced glutathione depletion (GSH), Nitric oxide (NOx) and malondialdehyde (MDA), thioredoxin (Trx) contents and elevated nuclear factor erythroid 2–related factor 2 (Nrf-2) content. Its anti-inflammatory effects were confirmed by observing a decrease in nuclear factor-κB (NF- κβ), interleukin-1b (IL-1β) and inducible nitric oxide synthase (iNOS) content. The anti-fibrotic effects of SCCWE were explored by assessing fibrosis related markers as it significantly reduced transform growth factor-β (TGF-β) and autotaxin (ATX) contents. Administration of SCCWE significantly decreased matrix metalloproteinase-3 and 9 (MMP-3 and -9). Furthermore, it also decreased alpha smooth muscle actin (α-SMA) and caspase-3 as assessed immunohistochemically those results were similar to that of the standard drug UDCA. This study shows that SCCWE protects against TAA-induced liver fibrosis in rats, through attenuating oxidative stress, and inflammation, ameliorating MMPs, combating apoptosis and thereby fibrotic biomarkers in addition to improving histopathological changes. Abstract : SCCWE; TAA; Liver fibrosis; Oxidative stress; Inflammation; MMPs; Apoptosis; TGF-β; α-SMA; ATX